Polskie pisarstwo kobiet w wieku XX: procesy i gatunki, sytuacje i tematy - Redakcja (Wydawnictwo Naukowe UAM, 2015)
Wieloautorski tom to cenna monografia, a zarazem podręcznik do historii literatury polskiej XX w. uwzględniający równorzędny udział kobiet-pisarek w tworzeniu piśmiennictwa narodowego. Będzie to nie tylko obowiązkowa polonistyczna synteza uniwersytecka oraz lektura uzupełniająca dla przedstawicieli innych dziedzin humanistyki, lecz także książka zaspokajająca gusty wszelkich miłośników i znawców polskiej kultury dwudziestowiecznej. Część pierwsza, „Procesy i gatunki”, stawia sobie za cel ukazanie procesu historycznoliterackiego z perspektywy genderowej oraz opis genologiczny dwudziestowiecznego pisarstwa kobiet. W części drugiej, „Sytuacje i tematy”, zostają poddane refleksji m.in. związki uczuciowo-intelektualne między pisarkami, miejsce kobiety-pisarki w komunikacji literackiej, doświadczenie Zagłady, wojny i emigracji w pisarstwie kobiet, status pisarki regionalnej, humor w kobiecych narracjach osobistych, przeszłość i historia w pisarstwie kobiet, różne wymiary religijności w liryce kobiecej oraz problematyka cielesności w poezji i prozie kobiecej.

The volume presents a panorama of writings by twentieth-century Polish women analyzed from different perspectives and in a variety of contexts. The introductory chapters of Part One contain a diachronic outline of the processes through which women writers contributed to the general history of Polish modem literature and culture, as well as discussion on the specificity of their works. It is argued here, among other things, that the emancipatory success of the modem woman was closely intertwined with the emergence of the professional woman writer on the literary scene, and some outstanding Polish examples - such as Maria Rodziewiczówna, Gabriela Zapolska, Maria Komornicka, Marcelina Kulikowska - of this universal cultural mechanism are thoroughly examined. The preliminary inquiries are preceded by a summary of Polish literary criticism of women's writing from its nineteenth-century beginnings to the present-day proliferation of academic research on the subject. The subsequent chapters present a selection of genres of women's writing and their development in the course of the twentieth century: the female Bildungsroman, women's psychological fiction, women's poetry, drama, and journalistic writing. The last chapter of Part One is devoted to women as translators of literary works. Part Two of the volume focuses on "situations" and "topics". The former category pertains to various interpersonal (official, family, lesbian, etc.) relations among women writers, whereas the latter encompasses specific feminine conceptualizations of such issues as the past, war and the Holocaust, exile, humour, religion, bodily experiences, etc. Among the many women authors whose works are evoked here are such renown names as Zofia Nałkowska, Maria Dąbrowska, Maria Pawlikowska-Jasnorzewska, Wisława Szymborska, Julia Hartwig; however, a lot of research focuses also on minor or even forgotten female authors who are thereby brought back from oblivion. As a result, what the volume presents is in many respects a revision of literary hierarchies and syntheses prevailing in the history of Polish literature of the 20th century.
20th Century Women’s Writing in Poland: Processes and Genres, Situations and Topics
Keywords: literatura polska XX w.; dwudziestowieczne pisarstwo kobiet; wojna w pisarstwie kobiet